2014
DOI: 10.1177/0022034514549378
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors and the Risk of Osseointegrated Implant Failure

Abstract: Selective serotonin reuptake inhibitors (SSRIs), the most widely used drugs for the treatment of depression, have been reported to reduce bone formation and increase the risk of bone fracture. Since osseointegration is influenced by bone metabolism, this study aimed to investigate the association between SSRIs and the risk of failures in osseointegrated implants. This retrospective cohort study was conducted on patients treated with dental implants from January 2007 to January 2013. A total of 916 dental impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 30 publications
8
102
3
Order By: Relevance
“…A study (Wu et al. ) observed that treatment with selective serotonin reuptake inhibitors (SSRIs – a class of antidepressive drugs) is associated with an increased failure risk of osseointegrated implants. Some animal models (Warden et al.…”
Section: Discussionmentioning
confidence: 99%
“…A study (Wu et al. ) observed that treatment with selective serotonin reuptake inhibitors (SSRIs – a class of antidepressive drugs) is associated with an increased failure risk of osseointegrated implants. Some animal models (Warden et al.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Ti dental implants have shown excellent survival rates in the past years, 4 however, the issue of bacterial colonization remains a problem as biofilm formation on the implant surface can lead to loss of osseointegration with subsequent treatment failure. [5][6][7] Thus, many chemical disinfection protocols have been developed to try and clean implants after surface infection, in hopes of avoiding surgical intervention and increase the survival rates of affected implants. 8 Biofilm formation comprises of a series of stages, starting with the initial adhesion of early colonizing species 9 and continued by the attachment of secondary and increasingly pathogenic bacteria that can lead to disease.…”
Section: Introductionmentioning
confidence: 99%
“…99,103,104,111,112,117 clearly defined what kind of smoking patients were included in their studies based on how many cigarettes the patients used to smoke per day.Fig. 1 -Study screening process.…”
mentioning
confidence: 99%